2021
DOI: 10.1111/cns.13650
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Toxoplasma gondii infection and sleep‐wake alterations in mice

Abstract: Aim Toxoplasma gondii (Tg) is an intracellular parasite infecting more than a third of the human population. Yet, the impact of Tg infection on sleep, a highly sensitive index of brain functions, remains unknown. We designed an experimental mouse model of chronic Tg infection to assess the effects on sleep‐wake states. Methods Mice were infected using cysts of the type II Prugniaud strain. We performed chronic sleep‐wake recordings and monitoring as well as EEG power spectral density analysis in order to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…In an experimental mouse model of chronic T . gondii infection, investigators found that infected mice exhibited chronic sleep–wake alterations over months, including a marked increase in time spent awake [ 25 ]. Further research to determine the association between insomnia and T .…”
Section: Discussionmentioning
confidence: 99%
“…In an experimental mouse model of chronic T . gondii infection, investigators found that infected mice exhibited chronic sleep–wake alterations over months, including a marked increase in time spent awake [ 25 ]. Further research to determine the association between insomnia and T .…”
Section: Discussionmentioning
confidence: 99%
“…It is worth considering the role of circadian rhythms on other neurotrophic pathogens, many of which can establish chronic infection and alter sleep rhythms, as demonstrated for Toxoplasma gondii [ 136 ]. Interestingly, crosstalk between the brain and daily changes in gut microbiota was shown to contribute to aging-associated neurodegenerative diseases [ 137 ].…”
Section: Interplay Between Clocks and Pathogens In Different Host Nichesmentioning
confidence: 99%